Updated extinction risk of seagrass species in the Tropical Atlantic Bioregion - Samper-Villarreal, Jimena; Creed, Joel C.; Frade, Duarte; Furman, Bradley T.; Bandeira, Salomão; El-Hacen, Hacen M.; Peralta, A. Carolina; Serrão, Ester A.; Vera Vegas, Beatriz E.; van Tussenbroek, Brigitta I. (Frontiers in Conservation Science, 2025)
Seagrasses can form vast meadows in coastal areas and provide valuable ecosystem services. Despite their importance, seagrasses are threatened, and their spatial extent and ecological condition have declined worldwide. Globally, there are six seagrass bioregions based on ocean basin and species distribution. The Tropical Atlantic Bioregion encompasses seagrasses in the warm waters off the Atlantic American continent, the eastern Pacific and the west coast of Africa. Here, the extinction risk of the species was determined through the Categories and Criteria of the IUCN Red List of Threatened Species. The extinction risk for the 15 native seagrass species in the bioregion was assessed and summarized as an update to the previous IUCN effort, conducted 15 years ago. The updated regional assessments were based on expert opinion and compilation of revised data on species´ distribution, population status and trend. Of the 15 native species, nine were endemic to the bioregion; thus, the regional assessment was also a global one. Two other species were typical for the region but also occurred beyond bioregional boundaries (Halodule beaudettei and H. wrightii). The remaining species were either distributed circumglobally (2 species), or consisted of peripheral populations of species characteristic of neighboring bioregions (2 species). The detailed information of 15 assessments have been made freely accessible in an open repository. Nine species maintained their previous risk of extinction status, while one species (Thalassia testudinum) changed from the Least Concern to the Near Threatened category. Downgrading of the status of T. testudinum is worrying, as this is the dominant climax species in the wider Caribbean. Its replacement by less resistant and smaller but faster growing species, such as Syringodium filiforme and H. wrightii (both classified as Least Concern), could compromise the ecosystem services of seagrasses in this bioregion. An additional two species had been recently introduced, and are also briefly covered. The assessments included past and present taxonomical uncertainties of various assessed species. Issues concerning the current boundaries of the bioregions themselves were also encountered. To address this and better capture future and ongoing range expansion or reduction associated with climate change, we propose overlapping transitional boundaries with neighboring seagrass bioregions.